A feasibility study on Time Pers a resting facility - Balangatan, Erwin; Longalong, Annabelia; Ocampo, Carlo Norberto F.; Rodriguez, Frederick Charles
Time Pers is a resting facility aiming to give a venue for resting to students in their free times. Students, in general, have limited budget, and may not have much to spare to pay for the service offered. Attractive rates will ensure that the market will avail of the service. However, attractive rates are not enough to keep an organization afloat. A thorough market research was done regarding the market feasibility of Time Pers. Surveys were conducted to determine the target market and the perceived rate for the service. Data gathered proved that there is sufficient demand to justify the implementation of the project. Also, various marketing strategies, promotions, and proper placements were evaluated as well as calculations of related costs to these activities. Finally, a marketing and budget plan was developed in order to help the facility project its profitability in the foreseeable future. Time Pers requires a simple construction task for the shell of the facility while its requirements like bed frames and air-conditioners are commercially available. The material inputs to the service like blankets and pillows are also easy to obtain while the people offering laundry service for the facility are also abundant. The process of the service is simple while the technological requirements for the service are also minimal. Labor requirements are also easy to fulfill since, at most, only two regular workers are needed while marketing and maintenance personnel are only needed around once a month. Technical requirements of the project are sustainable making the project technically feasible. After thorough analysis and evaluation of the financial study, it is concluded that the project is financially feasible since it operates profitably, generates sufficient cash and generates acceptable returns to its investors. These findings are backed up by financial projections and their subsequent analyses. In general, the organization and management of Time Pers is small and simple. Coupled with the fact that positions are to be occupied by the proponents themselves, it can be safely assumed that the major factor in the study of the organization structure and its various functions is the minimization of costs. After a thorough analysis of the data and various socio-economic criteria, the social profitability study proves that the facility is an acceptable project within the duration of its life.